2018
DOI: 10.30548/vascfail.2.2_80
|View full text |Cite
|
Sign up to set email alerts
|

Arginine deficiency measured by global arginine bioavailability ratio in patients with acute coronary syndrome

Abstract: Background: L-arginine and its related metabolites are associated with arginine bioavailability and subsequent nitric oxide production. The global L-arginine bioavailability ratio (GABR), defined as the ratio of the level of L-arginine to the sum of the levels of its major metabolites (L-arginine/[L-citrulline + L-ornithine]), has been reported as an index of arginine bioavailability. GABR in acute coronary syndrome (ACS) has not been fully investigated. Methods and results: The serum levels of L-arginine, L-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
(44 reference statements)
0
3
1
Order By: Relevance
“…We recently investigated GABR in the emergency setting of acute coronary syndrome (ACS). GABR was significantly decreased in the ACS group compared with the non-ACS group (i.e., stable patients undergoing coronary angiography), but we could not find any significant difference in GABR according to the presence or absence of CAD in the non-ACS group 14) . In that study, patients in the non-ACS group who did not have coronary stenosis had undergone coronary angiography for reasons such as symptoms or signs compatible with coronary ischemia.…”
Section: Introductioncontrasting
confidence: 75%
“…We recently investigated GABR in the emergency setting of acute coronary syndrome (ACS). GABR was significantly decreased in the ACS group compared with the non-ACS group (i.e., stable patients undergoing coronary angiography), but we could not find any significant difference in GABR according to the presence or absence of CAD in the non-ACS group 14) . In that study, patients in the non-ACS group who did not have coronary stenosis had undergone coronary angiography for reasons such as symptoms or signs compatible with coronary ischemia.…”
Section: Introductioncontrasting
confidence: 75%
“…Patients with cardiogenic shock due to acute myocardial infarction (AMI) have been reported to have a lower GABR compared with patients with stable CAD 25) . We also previously reported that the GABR is lower in patients with acute coronary syndrome (ACS) [26][27][28] . Thus, many cross-sectional studies have examined amino acid profiles; however, long-term mortality according to the amino acid profile has not been fully investigated.…”
Section: Coronary Risk Factorsmentioning
confidence: 83%
“…Increased arginase activity in endothelial cells may lead to endothelial dysfunction by decreasing the concentration of l-arginine available for NO production. Another possibility may be the decreased bioavailability of arginine by metabolites of studies, arteriosclerosis, CAD, and ACS were found to be strongly associated with the bioavailability of l-arginine 26,27,[47][48][49] . Decreased l-arginine bioavailability is likewise associated with obesity, insulin resistance, catabolic metabolites, l-ornithine and l-citrulline, during urea synthesis, a low l-arginine/l-ornithine ratio indicates decreased l-arginine bioavailability with increased arginase activity.…”
Section: Cox Regression Analysis For the Primary And Secondary Endpointsmentioning
confidence: 99%
“…The activation of the urea cycle and inducible NO synthase could increase these metabolites [ 28 ]. Increases in the ornithine/arginine ratio or a decrease in GABR (Arg/Cit+Orn) were associated with cardiovascular events [ 29 , 30 ], which were observed in HFHSD-LE2KO. The deterioration in HST and abnormal arginine metabolism may contribute to cardiovascular risk and diseases.…”
Section: Discussionmentioning
confidence: 99%